2005
DOI: 10.1097/01.inf.0000157213.94392.30
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Scedosporium Prolificans Infection and Survival of a Child With Acute Lymphoblastic Leukemia

Abstract: Scedosporium prolificans is a saprophytic fungus responsible for an increasing number of infections among immunocompromised hosts. Historically, disseminated infection with this organism has resulted in death. We report on a pediatric patient who developed overwhelming S. prolificans sepsis after induction chemotherapy for acute lymphoblastic leukemia. She is well 18 months after the diagnosis of fungal sepsis and continues to receive chemotherapy for leukemia, which remains in remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 17 publications
0
19
0
1
Order By: Relevance
“…The most common isolate was S. prolificans, accounting for over a third of cases. Since that review, S. prolificans remains the most frequent cause of disseminated disease, almost exclusively in immunocompromised patients (33,62,96,151,304,358,364,368,434,697,709,747,750,796). E. dermatitidis, in contrast, is commonly seen in immunocompetent patients, particularly from Asia (13,349,565).…”
Section: Phaeohyphomycosismentioning
confidence: 99%
See 2 more Smart Citations
“…The most common isolate was S. prolificans, accounting for over a third of cases. Since that review, S. prolificans remains the most frequent cause of disseminated disease, almost exclusively in immunocompromised patients (33,62,96,151,304,358,364,368,434,697,709,747,750,796). E. dermatitidis, in contrast, is commonly seen in immunocompetent patients, particularly from Asia (13,349,565).…”
Section: Phaeohyphomycosismentioning
confidence: 99%
“…There were no antifungal regimens associated with improved survival for disseminated infection. Scedosporium prolificans is generally resistant to all available antifungal agents, and infection with S. prolificans was associated with nearly 100% mortality in the absence of recovery from neu- (358,750,796). Some case reports utilized colony-stimulating factors and/or leukocyte infusions to augment antifungal therapy (96,368,796).…”
Section: Phaeohyphomycosismentioning
confidence: 99%
See 1 more Smart Citation
“…are among the most antifungal drug-resistant organisms encountered in clinical practice (1,2,7,21,25,32,38). Optimal treatment against infection with these fungal pathogens has not been established, and anecdotal successes have been reported with various agents alone or in combination (4,12,14,18,20,23,26,33,34,40).…”
mentioning
confidence: 99%
“…21,31 Since the first case of scedosporiosis reported in acute leukemia in 1977, 32 hematologists have shown a growing interest in this pathogen, particularly over the last decade. Both our literature review and our case series demonstrated that, among patients affected by hematologic malignancies, those affected by AML are at the highest risk, usually during a period of chemotherapy induced severe neutropenia.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%